Secondary Spontaneous Pneumothorax in a High-TB-Burden Region: Incidence, Aetiology and Short-term Outcomes - Dr Shagun; Dr Sunil Sharma; Dr Malay Sarkar; Dr RS Negi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Secondary spontaneous pneumothorax (SSP) produces greater morbidity and recurrence than primary disease. Contemporary data from tuberculosis (TB)–endemic regions are sparse. Objectives: (i) Quantify SSP incidence among consecutive pneumothorax presentations in a North-Indian tertiary centre; (ii) delineate the current aetiological spectrum; (iii) describe two-hour radiographic response and early complications after guideline-adapted management; and (iv) identify 12-month recurrence predictors. Methods: Adults with radiologically confirmed pneumothorax were enrolled prospectively. SSP was defined as pneumothorax with underlying lung disease. Management followed British Thoracic Society (BTS-2023) algorithms. Primary outcome was full lung re-expansion two hours post-intervention; secondary outcomes were early complications and recurrence at 12 months. Predictors of recurrence were examined with multivariate Cox analysis. Results: Of 111 pneumothoraces, 75 (67.6 %) were SSP (median age 62 y; M:F = 6.3:1). TB—active 21.3 % plus post-TB sequelae 22.7 %—superseded COPD (40 %) as the leading cause. Heavy smoking index ≥ 300 pack-year-equivalents occurred in 50.7 % of SSP versus 11 % of non-SSP (p < 0.001). Intercostal drainage (ICD) was required in 94.7 % of SSP; two-hour full re-expansion reached 61.3 %. Sub-cutaneous emphysema (57 %) predominated among early complications. Twelve-month recurrence was 14.7 %; underlying TB (HR 2.1, 95 %CI 1.1–4.3) and persistent air-leak > 5 days (HR 3.4, 1.4–7.9) were independent predictors. Conclusions: In high-TB settings, TB now rivals COPD as the principal driver of SSP. Prompt small-bore ICD ensures rapid re-expansion, yet appreciable early recurrence supports first-episode pleurodesis and intensified smoking-cessation strategies.